2022
DOI: 10.48550/arxiv.2204.07816
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

$2^{1296}$ Exponentially Complex Quantum Many-Body Simulation via Scalable Deep Learning Method

Abstract: For decades, people are developing efficient numerical methods for solving the challenging quantum many-body problem, whose Hilbert space grows exponentially with the size of the problem. However, this journey is far from over, as previous methods all have serious limitations. The recently developed deep learning methods provide a very promising new route to solve the long-standing quantum many-body problems. We report that a deep learning based simulation protocol can achieve the solution with state-of-the-ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…1(a) for a depiction of an RBM. Together with RBMs [2,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], other network structures such as a feed-forward [34][35][36][37][38], recurrent [39,40] and convolutional neural networks [41][42][43][44][45][46][47][48][49][50][51][52] have also been intensively studied. The significant interest in the field is attributed to the fact that these networks could offer possibility to fight against the curse of dimensionality in many-body quantum systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1(a) for a depiction of an RBM. Together with RBMs [2,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], other network structures such as a feed-forward [34][35][36][37][38], recurrent [39,40] and convolutional neural networks [41][42][43][44][45][46][47][48][49][50][51][52] have also been intensively studied. The significant interest in the field is attributed to the fact that these networks could offer possibility to fight against the curse of dimensionality in many-body quantum systems.…”
mentioning
confidence: 99%
“…Different strategies have been studied in order to improve the accuracy and speed of convergence of neural network quantum states algorithms, such as transfer learning [20], pruning [24], importance sampling [44], and massive parallelization [52]. Between these different techniques, it has been consistently shown that stochastic reconfiguration [56], effectively a Hessian based optimization routine motivated by imaginary time evolution, can provide significantly better performance.…”
mentioning
confidence: 99%